(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: هدفت الدراسة الحالية إلى الكشف عن فعالية برنامج تدريبي قائم على التخيل المعرفي لتحسين الإدراك لدى تلاميذ الرابعة ابتدائي ذوي صعوبات التعلم. تمّ إجراء الدراسة على عينة قوامها (10) تلاميذ، من تلاميذ الرابعة ابتدائي ذوي صعوبات التعلم، يزاولون دراستهم بابتدائية " عبد الرزاق بالقط " بالوادي، تتراوح أعمارهم بين (10ــ 11) سنة، ولتحقيق أهداف الدراسة، تمّ استخدام المصفوفات الملونة "لرافن " لقياس الذكاء، ومقياس صعوبات التعلم للسرطاوي والمقياس التشخيصي لصعوبات الإدراك (البصري، السمعي، الحركي) للزيات، والبرنامج التدريبي الموجه للتلاميذ بهدف تحسين الإدراك. وباعتماد المنهج التجريبي القائم على تصميم المجموعة الواحدة بقياس قبلي وبعدي، وباستخدام المتوسط الحسابي والانحراف المعياري واختبار(ت) توصلت الدراسة إلى النتائج الآتية: توجد فروق دالة إحصائيا بين القياس القبلي والقياس البعدي لأفراد العينة في مستوى صعوبة الإدراك البصري، ومستوى صعوبة الإدراك السمعي، ومستوى صعوبة الإدراك الحركي لصالح البعدي. كلمات دالة: برنامج تدريبي،التخيل المعرفي،الإدراك،ذوي صعوبات التعلم،فعالية. Abstract: The current study aimed at examining the effectiveness of a training program based on cognitive imagination to improve the perception of fourth primary students with learning disabilities. The study was conducted on a sample of (10) students, from the fourth primary students with learning difficulties, in the elementary "Abdul Razzaq Balqot" in Eloued, between (10-11) years, to achieve the objectives of the study ,we used colored matrices "Raven", the learning difficulties scale for saratqoui, and the diagnostic scale for perception difficulties of Al-Zayyat, and the training program. by adopting the experimental approach based on one group design with pre and post measurement, and using the arithmetic mean, standard deviation and t-test, the study reached the following results: There are statistically significant differences between the pre-measurement and the post-measurement of the sample in the level of difficulty in visual, auditory,and motor perception in favor of the post-measurement. Key words: Training program, cognitive imagination, perception, people with learning disabilities, effectiveness.